2022
DOI: 10.3390/nano12081318
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and Comprehension of Electronic and Topographic Contrasts on Cooperatively Switched Diarylethene-Bridged Ditopic Ligand

Abstract: Diarylethene is a prototypical molecular switch that can be reversibly photoisomerized between its open and closed forms. Ligands bpy-DAE-bpy, consisting of a phenyl-diarylethene-phenyl (DAE) central core and bipyridine (bpy) terminal substituents, are able to self-organize. They are investigated by scanning tunneling microscopy at the solid–liquid interface. Upon light irradiation, cooperative photochromic switching of the ligands is recognized down to the submolecular level. The closed isomers show different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Scanning tunneling microscopy (STM) is a powerful tool to visualize the molecules inside nanostructures. ,, , It can be employed to investigate the electronic contrasts at a submolecular level, ,, which is very challenging at the solid/liquid interface. In the present work, we focus on two comparable ditopic terpyridine-terminated molecules connected by single (-Fluo-) or double (-bisFluo-) fluorene.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning tunneling microscopy (STM) is a powerful tool to visualize the molecules inside nanostructures. ,, , It can be employed to investigate the electronic contrasts at a submolecular level, ,, which is very challenging at the solid/liquid interface. In the present work, we focus on two comparable ditopic terpyridine-terminated molecules connected by single (-Fluo-) or double (-bisFluo-) fluorene.…”
Section: Introductionmentioning
confidence: 99%
“…This adsorbate adopts a normally unstable Sshaped conformation when integrated into a 2D layer, which was explained by the stabilization through a combination of hydrogen bond formation and van der Waals interactions. 32 Similar results were reported by Hnid et al 33 for a derivative of diarylethene functionalized with bipyridine ligands, which possesses two isomers in the form of a closed and open structure. It was shown that the normally metastable closed form becomes predominantly populated when adsorbed on the HOPG surface, which was attributed to the stabilization via a combination of hydrogen bonds and van der Waals interactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7,8 Switching of molecules or their self-assemblies have be triggered by means of chemical, optical, thermal, electrical or electrochemical stimulation at various scales, or down to the molecular level. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Once assembled on a surface, molecules can be directly visualized by Scanning Tunneling Microscopy (STM). [24][25][26][27] Thanks to sub-molecular level STM imaging, it is possible to recognize different molecular switches or reactions which lead to long-range supramolecular reorganizations on surfaces.…”
mentioning
confidence: 99%